THERMAL EXPANSION OF SOLIDS - Bozorov Nosirjon Sodikovich; Umurkulov Kayumjon Parpievich; Alisherov Otabek Alisher ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article presents the basic assumptions about the thermal expansion of solids and their thermal conductivity. It is shown that the coefficient of linear expansion α is proportional to the heat capacity of the body. In the region of high temperatures, the energy of linearly oscillating particles is equal to E = qD. In the region of low temperatures, α behaves similarly to Cv: it decreases with decreasing temperature and tends to zero as it approaches absolute zero.